Mediating effect of teacher empowerment between entrepreneurial leadership and school effectiveness - Dahiru, Abbas Sani; Lope Pihie, Zaidatol Akmaliah; Basri, Ramli; Hassan, Siti Aishah (Medwell Journals, 2017)
This study intends to investigate the mediating effect of teacher empowerment between entrepreneurial leadership and school effectiveness. The research adopted a correlational design with a total sample of 358 teachers in Zamfara State, Nigeria. Data was collected through survey method and was analyzed using both descriptive and inferential (structural equation modeling) statistics analysis. The findings of the study indicated that there is a significant relationship between entrepreneurial leadership, teacher empowerment and school effectiveness. Furthermore, teacher empowerment was found to be a mediator between entrepreneurial leadership and school effectiveness. This implies that the relationship between entrepreneurial leadership and school effectiveness is better enhanced through teacher empowerment.